Analysis of the Influence of Chinese Ethnic Youth's Independent Enterprises on Labor Absorption in Medan Kota District Area, Medan City - Tri Utari Imayuni; Jhon Piter; Mariska Sisilia; Rio Brandlee; Kartina Rahmadani Rambe; Abdal Ahmed (Digital Innovation : International Journal of Management, 2025)
One of the districts with the greatest concentration of ethnic Chinese residents and the highest concentration of young business owners in Medan City is Medan Kota District. The purpose of this study is to clarify the potential impact of ethnic Chinese youth's independent enterprises on labor absorption in Medan Kota District. A quantitative descriptive research design is employed, and SPSS version 17 analysis is used to perform the Multiple Linear Regression research method. Ho was rejected while Ha was accepted, according to the ANOVA test, which revealed that Fcount> Ftable. This indicates that ethnic Chinese youth-owned independent enterprises significantly improve labor absorption, specifically 72%.